Should Readmission Within 30 Days After Discharge of Children Hospitalized for a Neurologic Disorder Be Considered a Quality Assurance Failure?. (June 2013) - Allred, Elizabeth; An, Sookee; Leviton, Alan; Loddenkemper, Tobias; McCrave, Jennifer; Nichol, Sarena Michell
The Affordable Care Act penalizes hospitals with high readmission rates. Children's hospitals are not yet among these hospitals, although that is likely to change. Because chronic neurologic conditions represent a sizable proportion of all children's hospitals costs, and because some/many of the readmissions might not be easily prevented, children's hospitals and neurologists who care for children might be inappropriately penalized for some readmissions. We encourage more study to identify the correlates of readmission of children who have a neurologic disorder.